2010
DOI: 10.1016/j.ophtha.2010.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Nylon Foil-Anchored Polytetrafluoroetyhlene (Gore-Tex) Sheet Stenting for Conjunctival Fornix Reconstruction

Abstract: Purpose To describe a surgical technique that deepens foreshortened conjunctival fornices by providing a scaffold for epithelialization that opposes contractile forces during wound healing. Design Retrospective interventional case series Participants Seventeen patients with anophthalmic sockets containing foreshortened conjunctival fornices Methods Conjunctival fornices was reconstructed with stents of expanded polytetrafluoroethylene (e-PTFE) sheet draped over rigid, 0.8 mm thick nylon strips that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The general principle of socket reconstructive techniques is excision of the conjunctival scarred tissues, followed by graft or flap placement to replace lost conjunctiva and enlarge the forniceal space [ 2 ]. Several grafts are mentioned in the literature, including oral mucosa, [ 2 , 3 , 7 ] hard palate, [ 6 , 8 ] skin graft, [ 9 , 10 ] dermis fat graft, [ 11 ] and polytetrafluoroethylene [ 12 , 13 ]. Previous studies have reported that using a full-thickness mucous membrane graft, which allows the grafted tissue to match the conjunctiva histologically, is successful in almost all degrees of contractions [ 3 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general principle of socket reconstructive techniques is excision of the conjunctival scarred tissues, followed by graft or flap placement to replace lost conjunctiva and enlarge the forniceal space [ 2 ]. Several grafts are mentioned in the literature, including oral mucosa, [ 2 , 3 , 7 ] hard palate, [ 6 , 8 ] skin graft, [ 9 , 10 ] dermis fat graft, [ 11 ] and polytetrafluoroethylene [ 12 , 13 ]. Previous studies have reported that using a full-thickness mucous membrane graft, which allows the grafted tissue to match the conjunctiva histologically, is successful in almost all degrees of contractions [ 3 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expended polytetrafluoroethylene (e-PTFE) is a high polymer material for medical use, and due to its characteristics of inertia, microporous structure and corrosion resistance[ 1 ], it has broad applications in biomedical engineering. For example, the membrane tube implant made of e-PTFE membrane and silicone tube can be used to treat refractory glaucoma[ 2 ]; the covered stent covered by e-PTFE cab effectively alleviate the refractory ascites of liver cirrhosis patients[ 3 ]; the e-PTFE flake stent anchored with rigid nylon foil can be used in the reconstruction of fornical conjunctiva[ 4 ]; the e-PTFE soft tissue patch and vascularized flap can be used in the chest wall reconstruction of patients who had chest wall resection[ 5 ]. With more clinical applications, e-PTFE has gradually replaced the traditional silicone rubber and become one of the most ideal biological tissue substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…However, even after careful and meticulous surgical manipulations, repeated socket contraction can occur. 8 Mitomycin-C (MMC) is an alkylating antimetabolite agent which acts by inhibiting DNA synthesis with significant ability to suppress fibroblasts proliferation and activity, thus causing a significant reduction of scarring in vitro and in vivo. MMC has been used successfully in glaucoma surgery to prevent recurrence by inhibiting subconjunctival fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, even after careful and meticulous surgical manipulations, repeated socket contraction can occur. 8 …”
Section: Introductionmentioning
confidence: 99%